Brand Management Advancing Insights on - Popoli, Paolo (IntechOpen, 2017)
This book is an original, high-quality collection of chapters about highly topical and important brand management issues, and it shows both theoretical and empiric analysis. The 10 selected chapters are referred, with original contents and rigorous research methodologies, to some important challenges the brand management has to face in the current competitive contexts, characterized by the dominance of the intangible resources and the new information and communication technologies. Written by leading academics, this book is dedicated not only to marketing and management scholars but also to students wanting to investigate the knowledge concerning special fields and special brand management themes. As well to the practitioners who can find a wide reference also to the managerial implication from the strategic and operative perspectives.